Identification and application of species-specific peptide biomarkers from soft-shelled turtles (Pelodiscus sinensis) using post-translational modification detection-based peptidomics analysis. (1st September 2023) - Xia, Haoran; Liu, Xun; Cai, Shuo; Chen, Shengjun; Li, Song; Zhao, Ming; Duan, Jin-ao; Liu, Rui; Han, Shuying
Highlights: PTM detection-based peptidomics analysis was applied to identify specific peptide biomarkers. Eight Pelodiscus sinensis specific peptide sequences were selected. 74 specific peptide biomarkers derived from 8 sequences with various PTM forms were identified. Seven specific peptide biomarkers were screened out and could be used to discern authenticity. Abstract: The soft-shelled turtle is a commercially aquatic species in Asian countries, which serves as an important source of collagen with high nutritional and medicinal value, so it is of great significance to distinguish soft-shelled turtle derived collagen from others or adulterations. In this work, peptidomics analysis based on post-translational modification (PTM) assay was used to discover specific peptide biomarkers of soft-shelled turtle gelatin (STG). In total eight specific sequences and 74 peptides with different PTM types were screened out, and seven peptides with good signal responses and STG specificity were selected and validated as STG-specific peptide biomarkers. These peptide biomarkers could be used for distinguishing STG from other animal gelatins, and applied for ensuring the quality of collagens or gelatins from soft-shelled turtle with authenticity and traceability.